2008
DOI: 10.1111/j.1365-3059.2008.01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of pathogenicity genes in Xanthomonas oryzae pv. oryzae by transposon mutagenesis

Abstract: A transposon mutant library was constructed from the bacterial blight pathogen Xanthomonas oryzae pv . oryzae ( Xoo ) KACC10331 by Tn5 transposon mutagenesis. The susceptible rice cultivar Milyang 23 was inoculated with a total of 24 540 mutants resistant to kanamycin and 67 avirulent or reduced-pathogenicity mutant strains were selected for study. Southern hybridization verified that 84 mutant strains had single-copy insertions and their single-transposon insertion sites were identified by sequencing analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Mutations in pilY1 , pilQ , pilM , pilZ and pilT genes resulted in reduced virulence in X. oryzae pv. oryzicola (Wang, So, Park, Lee & Kang, ). A pilQ mutant expressed reduced twitching motility and biofilm formation (Lim et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in pilY1 , pilQ , pilM , pilZ and pilT genes resulted in reduced virulence in X. oryzae pv. oryzicola (Wang, So, Park, Lee & Kang, ). A pilQ mutant expressed reduced twitching motility and biofilm formation (Lim et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria, therefore, often secrete cell wall-degrading enzymes, which contribute to bacterial virulence and include, e.g., cellulases, xylanases, polygalacturonases, and amylases (2-6). It is assumed that the degradation of plant cell wall components by bacterial enzymes facilitates the acquisition of nutrients as well as the translocation of virulence factors into the host cell (7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Bacteria, therefore, often secrete cell wall-degrading enzymes, which contribute to bacterial virulence and include, e.g., cellulases, xylanases, polygalacturonases, and amylases (2-6). It is assumed that the degradation of plant cell wall components by bacterial enzymes facilitates the acquisition of nutrients as well as the translocation of virulence factors into the host cell (7)(8)(9)(10)(11)(12)(13)(14).Bacterial extracellular enzymes are often secreted by a type II secretion (T2S) system, which is a major virulence factor of many Gram-negative plant-pathogenic bacteria, including Ralstonia solanacearum and species of Erwinia and Xanthomonas (8,(15)(16)(17)(18). T2S is a two-step process that often requires the Sec system for protein transport across the inner membrane (IM) (18,19).…”
mentioning
confidence: 99%
“…Disruption of xrvA led to a significant reduction in virulence, a delay in HR elicitation, a decrease in EPS and DSF production and an increase in glycogen accumulation. Recently, screening of a transposon mutant library of a Korean Xoo strain, KACC10331, in rice also showed that Tn5 insertion in the xrvA gene (XOO2744) led to reduced virulence; however, the mutant was not characterized in further detail (Wang et al, 2008). The deduced protein encoded by xrvA possesses an H-NS domain.…”
Section: Discussionmentioning
confidence: 99%